Penerapan Model Pembelajaran Savi (Somatic, Auditory, Visualization, Intellectually) terhadap Kemampuan Mengenal Penanganan Cedera Metode Rice pada Siswa Sekolah Dasar - Amanda Junikha Sintia Putri; Muhamad Nur Rahmad; Setiyawan Setiyawan (Universitas Malahayati Lampung, 2025)
ABSTRACT Injuries have significant impacts on the global burden of disease, especially among children. Injuries related to play and sports are among the most common causes of injuries to children worldwide. Home and school environments are primary locations where such injuries frequently occur in children. Education aimed at enhancing students’ understanding of conditions that may endanger their health is crucial. One of the first aid methods for minor injuries that can be taught to elementary school students is the RICE (Rest, Ice, Compression, Elevation) method. This method effectively addresses pain and swelling from sprains, bruises, contusions, and strains. Implementing an engaging and enjoyable health education model is necessary for effectiveness with children. The SAVI (Somatic, Auditory, Visualization, Intellectually) learning model is one approach that can be implemented. This model combines physical movement, cognitive activities, and the use of all senses, that significantly impacts learning outcomes. The purpose of this research is to determine the effect of implementing the SAVI Learning Model on elementary school students' ability to recognize injury management using the RICE method. This research employed a quantitative method with a pre-experimental one-group pretest-posttest design without a control group. The samples were selected through probability sampling using a simple random sampling technique, totaling 48 respondents. Data were analyzed using the Wilcoxon signed rank test, with results showing a p-value of 0.000 ( 0.05). Based on this finding, it was concluded that implementing the SAVI learning model significantly improved elementary school students’ ability to recognize injury management using the RICE method. Keywords: Injury, SAVI Learning Model, RICE Method, Elementary School ABSTRAK Cedera memberikan dampak signifikan terhadap beban penyakit global, khususnya pada anak-anak. Cedera yang terjadi akibat permainan dan olahraga merupakan salah satu penyebab cedera yang paling umum di kalangan anak-anak di seluruh dunia. Lingkungan rumah dan sekolah merupakan dua tempat teratas di mana cedera sering terjadi pada anak. Edukasi untuk meningkatkan pemahaman anak tentang kondisi yang dapat membahayakan kesehatan mereka penting dilakukan. Salah satu pertolongan pertama cedera ringan yang bisa diajarkan kepada anak sekolah dasar adalah metode RICE (Rest, Ice, Compression, Elevation). Metode ini efektif dalam mengatasi rasa sakit dan pembengkakan akibat keseleo, memar, lebam, dan terkilir. Diperlukan model pendidikan kesehatan yang menarik dan menyenangkan agar lebih efektif bagi anak-anak. Model pembelajaran SAVI (Somatic, Auditory, Visualization, Intellectually) merupakan sebuah pendekatan yang bisa diimplementasikan. Model ini menyatukan gerakan fisik, aktivitas kognitif, dan pemanfaatan seluruh indera, yang berdampak besar pada hasil pembelajaran. Bertujuan untuk mengidentifikasi adanya pengaruh penerapan Model Pembelajaran SAVI terhadap kemampuan mengenal penanganan cedera menggunakan Metode RICE pada siswa sekolah dasar. Metode yang digunakan yakni kuantitatif dengan rancangan pre-eksperimental one group pretest-posttest tanpa kelompok kontrol. Pemilihan sampel dilakukan melalui probability sampling dengan teknik simple random sampling, melibatkan 48 partisipan. Data diolah menggunakan Wilcoxon Signed Rank Test, dan menghasilkan p-value sebesar 0,000 ( 0,05). Hasil analisis menunjukkan adanya pengaruh signifikan penerapan model pembelajaran SAVI terhadap kemampuan mengenal penanganan cedera menggunakan metode RICE pada siswa sekolah dasar. Kata Kunci: Cedera, Model Pembelajaran SAVI, Metode RICE, Sekolah Dasar